2005
DOI: 10.1097/01.hp.0000165873.12868.59
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Doses in the Surroundings of Patients Undergoing Nuclear Medicine Diagnostic Studies

Abstract: Dose rate measurements were performed at 0, 0.5, and 1 m from the external surface of 79 patients corresponding to the most frequent studies: 99mTc-cardiac with reinjection, 99mTc-cardiac single injection, 99mTc-bone scan, 99mTc-lung studies, and cardiac studies using 201Tl. Doses to staff, nearby patients, and the collective effective doses were estimated for the different working shifts and hospital areas. The estimated dose for nurses for 1 y was 518 microSv in the cardiology section and 338 microSv in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…At first, it is calculated by measurements obtained at a fixed distance from the patient and some authors also take into consideration the time spent with the patient at a constant distance to calculate the amount of expected radiation exposure to technicians (4,5). In the other method the calculation is based on the direct reading of data obtained from the electronic pocket dosimeter of radiation workers (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, it is calculated by measurements obtained at a fixed distance from the patient and some authors also take into consideration the time spent with the patient at a constant distance to calculate the amount of expected radiation exposure to technicians (4,5). In the other method the calculation is based on the direct reading of data obtained from the electronic pocket dosimeter of radiation workers (6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation dose or dose rates per application and in total to staff within a time period such as daily, monthly or annually can be determined by two different methods ( 3 , 4 , 5 , 6 , 7 , 8 ). At first, it is calculated by measurements obtained at a fixed distance from the patient and some authors also take into consideration the time spent with the patient at a constant distance to calculate the amount of expected radiation exposure to technicians ( 4 , 5 ). In the other method the calculation is based on the direct reading of data obtained from the electronic pocket dosimeter of radiation workers ( 6 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…80 It should be noted that nuclear imaging has similar radiation exposure doses for cardiac studies (8 to 12 mSv). 81 Specifically, technetium studies are on the lower end of this spectrum (6 to 8 mSev on average), and thallium studies have been reported as high as 27 mSv. 82 With the retrospective ECG-gating mode, scan data are acquired and available for the entire phase of the cardiac cycle.…”
Section: Radiation Exposure During Ct Angiographymentioning
confidence: 99%
“…10 One drawback of MDCT as compared with EBCT is the higher radiation exposure to the patient (Table 4). 10,11,[73][74][75][76][77][78][79][80][81][82][83][84] The x-ray photon flux expressed by the product of x-ray tube current and exposure time (mAs) is generally higher with MDCT. For example, 200 mA with 0.5-second exposure time yields 100 mAs in MDCT versus 614 mA (fixed tube current) with 0.1-second exposure time yields 61.4 mAs in EBCT.…”
Section: Radiation Dose For Cardiac Ctmentioning
confidence: 99%
“…Potential increases in both medical and occupational radiation exposure have become a more urgent and persistent issue with the increasing dissemination of PET imaging, which uses higher-photon-yield radiopharmaceuticals such as 18 F-FDG (1-3). Task-based analyses often point to the handling and administration of radioactive materials as a key contributor to increased dose to staff (4)(5)(6)(7).…”
mentioning
confidence: 99%